2018
DOI: 10.1097/aog.0000000000002735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Enhanced Recovery After Surgery Program on Opioid Use and Patient-Reported Outcomes

Abstract: Implementation of an ERAS program was associated with significantly decreased opioid use after surgery and improvement in key patient-reported outcomes associated with functional recovery after surgery without compromising pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 36 publications
4
88
0
3
Order By: Relevance
“…For example, economic recovery and return to work may lag behind emotional or physical dimensions of recovery. In one study, patients on an ERAS pathway reported return to mild or no fatigue in 10 days compared with 30 days for the pre-ERAS cohort, while returning to mild or no interference with walking after laparotomy was reported at a median of 5 days for ERAS patients compared with 13 days in the pre-ERAS group 177. Patients undergoing minimally invasive surgery on an ERAS pathway reported a return to mild or no interference with walking at a median of 2 days 152…”
Section: Resultsmentioning
confidence: 99%
“…For example, economic recovery and return to work may lag behind emotional or physical dimensions of recovery. In one study, patients on an ERAS pathway reported return to mild or no fatigue in 10 days compared with 30 days for the pre-ERAS cohort, while returning to mild or no interference with walking after laparotomy was reported at a median of 5 days for ERAS patients compared with 13 days in the pre-ERAS group 177. Patients undergoing minimally invasive surgery on an ERAS pathway reported a return to mild or no interference with walking at a median of 2 days 152…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, comprehensive prospective screening by a dedicated ERAS nurse includes all complications according to the principle of Clavien classification,13 meaning that even complications usually tagged as 'irrelevant' were included here. This might contribute to a comparatively rather high complication rate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…23 In our study, the use of epidurals was negatively associated with complications for the group of complex surgery. Meyer et al 24 and Wijk et al 11 both showed a clear reduction in opioid consumption after introducing an ERAS protocol with multimodal pain treatment without epidurals, whereas Bergstrom et al 25 found a reduction in opioids in the ERAS population with an increased use of epidural. Approaches with multimodal oral pain management, often combined with alternative locoregional analgesia such as continuous lidocaine infusions, spinal analgesia or transversus abdominis plane blocks, or incisional injection also have been used successfully in gynecological ERAS protocols.…”
Section: Gynecology Original Researchmentioning
confidence: 99%